Naprężenia dynamiczne w cienkiej tarczy kołowej, wywołane działaniem nieustalonych źródeł ciepła - S. Woelke (Engineering Transactions, 1969)
In the paper the fields have been determined of temperature, displacements and dynamic stresses in a thin circular disk, caused by the action of heat sources of periodically varying and of constant output with time. The cases have been considered of the action of sources placed in a circle and within a circular region. The analysis of solutions obtained for heat sources with periodically varying output with time enabled to formulate the view that this kind of thermal forcing might be the cause of mechanical resonance vibration of the disk. The high resonance frequencies ensure that this type of mechanical resonance does not endanger machine constructions.